Moringa oleifera: Nature's health superstar / Nazatul Aqilah Ramlan and Faikah Awang @ Ismail - Ramlan, Nazatul Aqilah; Awang @ Ismail, Faikah (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The global surge in cancer rates is an increasingly concerning issue due to its ability to affect various organs and its potential for serious outcomes. The reasons behind the differing rates worldwide involve a complex mix of factors like genetics, lifestyle choices, and environmental influences. The consumption of processed foods and unhealthy habits, which are connected to a higher cancer risk, is particularly worrying. Figure 1 shows the most common cancers for men and women in Malaysia. As a response to the challenges posed by conventional cancer treatments and their side effects, there is a growing interest in exploring alternative approaches. Herbal treatments are gaining attention in this context, with Moringa oleifera standing out as a promising candidate. This tropical plant contains a range of beneficial compounds in its leaves, flowers, seeds, and other parts. These compounds, including vitamins, amino acids, flavonoids, and phenolic compounds, have shown potential for preventing and combating cancer.